Tinjauan Peran Majelis Taklim dalam Menanamkan Nilai-Nilai Islam di Desa Koto Teluk Kecamatan Hamparan Rawang - Lara Fitri, Shindi; Daflaini, Daflaini (Journal of Da'wah, 2022)
The assembly is a form of education emphasizes improving spiritual potential and developing the students or congregations so that they become the nobel spirit and faithful person to Allah SWT. The purposed of this study was to describes: (1) the role of the assembly in inculcating Islamic values in Koto Teluk Village, Hamparan Rawang District; (2) Islamic values taught to the assembly congregation in Koto Teluk Village, Hamparan Rawang District; (3) the activities of the assembly in Koto Teluk Village, Hamparan Rawang District. The design of this study was descriptive qualitative evaluative approach. The results of the study shown that the role of assemblies in inculcating Islamic values in Koto Teluk Village is as an environment for encouragement and developing religious life in order to create a society faithful to Allah SWT, a forum for friendship that fosters Islamic syi'ar and as a medium for conveying beneficial ideas for the people and nations development. The activities of the assembly in Koto Teluk Village are holding the Islamic discussion or recitation activities. The supporting factors in the inculcation of Islamic values are guidances from the chairman or ustad/ustadzah, facilities and infrastructure and the willingness of the assembly. While the obstructing factors are the physical condition which is unable to attend the recitation, either due to age or due to illness.